A Bridge Too Far? Distance to Waivered Physicians and Utilization of Buprenorphine Treatment for Opioid Use Disorder in West Virginia Medicaid. Issue 1 (December 2022) - Saloner, Brendan; Landis, Rachel K.; Jayakrishnan, Ritujith; Stein, Bradley D.; Barry, Colleen L.
Background : Travel distance to medication treatment for opioid use disorder (OUD) is a challenge for many patients, but little is known about how distance is associated with medication treatment utilization. This study examines the association between distance to the nearest physician waivered to prescribe buprenorphine and patient-level buprenorphine treatment among West Virginia Medicaid expansion enrollees with diagnosed OUD. Methods : We conducted a cross-sectional spatial analysis with 2016 Medicaid claims data, separately examining individuals living in metropolitan and non-metropolitan areas. We calculated the driving distance from the centroid of patients' residential ZIP codes to the street address of the nearest waivered physician derived from the 2015 Drug Enforcement Administration listing. Regression models examined the association between distance and initiation and duration of buprenorphine (among those initiating). Results : We focused on 8, 008 individuals with OUD in 2016. The nearest waivered prescriber in metropolitan areas was an average of 7.13 miles away from patients' residential ZIP codes and 14.54 miles in non-metropolitan areas. The providers they actually visited were a mean of 33.63 miles away in metro areas and 46.36 in non-metropolitan areas. In multivariable analyses, compared to those living <10 miles from a waivered physician, living >20 miles from a waivered physician was associated with −32.13 fewer days of treatment (95% CI: −57.86, −6.40) in metro areas and −16.70 fewer days in non-metro areas (95% CI: −32.32, −1.08). Conclusions : Longer travel distance to buprenorphine treatment is associated with a shorter duration of care that is likely to be clinically meaningful.